Caracterização físico-química dos óleos de castanha-do-Brasil e coco babaçu provenientes do projeto Sementes da floresta (Uruará-PA) - BONJARDIM, Rosana Silva (2021)
The Forest Seeds project, located in the municipality of Uruará in Pará, has been receiving support from the Socio- Environmental Institute in the development of actions that strengthen the productive chains of extractive products. The objective of this work was to analyze the physicochemical characteristics of refined coconut oils babassu and Brazil nuts produced by the project Seeds of the Forest. The analyzes were carried out in the Seeds and Plant Anatomy laboratory of the Federal University of Pará. The physicochemical parameters analyzed were: moisture content determination, density determination, acidity index, peroxide index and saponification index, employing the Adolfo Lutz Institute Analytical Standards and the American Oil Chemical Society (AOCS) standards. The results found for the indices of refined coconut oils babassu and Brazil nuts were, respectively: acidity (% lauric acid) of 0.0921 and 0.0930, humidity of 0.1601% w/w and 0.190% w/w, saponification of 246.7217 mg KOH/oil g and 190.2275 mg KOH/oil g, density 0.9058 g/ml and 0.9109 g/ml and peroxide 0.3255 mEq/kg and 4.8207 mEq/kg. The results are consistent with the standards employed, except for the saponification index of Brazil nut oil, which was not framed by the absence of specific standards.